Understanding and meeting injection device needs in multiple sclerosis: a survey of patient attitudes and practices - Russell S; Verdun di Cantogno E; Snow T (Patient Preference and Adherence, 2011)
Elisabetta Verdun di Cantogno1, Susan Russell2, Tom Snow21Global Clinical Development Unit, Merck Serono S.A. – Geneva, Switzerland; 2Global Marketing, Merck Serono S.A. – Geneva, SwitzerlandBackground: All established disease-modifying drugs for multiple sclerosis require parenteral administration, which can cause difficulties for some patients, sometimes leading to suboptimal adherence. A new electronic autoinjection device has been designed to address these issues.Methods: Patients with relapsing multiple sclerosis currently receiving subcutaneous or intramuscular interferon beta-1a, interferon beta-1b, or glatiramer acetate completed an online questionnaire (July 4–25, 2008) that surveyed current injection practices, experiences with current injection methods, and impressions and appeal of the new device.Results: In total, 422 patients completed the survey, of whom 44% used autoinjectors, 43% prefilled syringes, and 13% syringes and vials; overall, 66% currently self-injected. Physical and psychological barriers to self-injection included difficulty with injections, needle phobia, and concerns over correct injection technique. Only 40% of respondents were “very satisfied” with their current injection method. The new electronic autoinjector was rated as “very appealing” by 65% of patients. The benefits of the new device included the ability to customize injection settings and to review dosing history.Conclusion: New technologies may help patients overcome physical and psychological barriers to self-injection. The combination of a reliable and flexible autoinjection device with dose-monitoring technology may improve communication between health care professionals and patients, and improve treatment adherence.Keywords: adherence, autoinjection, subcutaneous interferon beta-1a, multiple sclerosis